2022
DOI: 10.7759/cureus.25651
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Outcomes of Depression After Bariatric Surgery: A Systematic Review and Meta-Analysis

Abstract: Surgeons often focus on weight loss and improvement of obesity-related conditions as a primary outcome after bariatric surgery. However, the success of bariatric surgery also relies on the improvement of mental health status. Therefore, the current meta-analysis was carried out to reveal the prevalence of depressive symptoms and their subsequent impact on bariatric surgery outcomes. This study was performed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 67 publications
0
17
0
8
Order By: Relevance
“…À longo prazo, estas medidas ampliam a redução de peso aumentando a eficácia da cirurgia e melhoram a qualidade de vida. Entretanto, para a compreensão destes efeitos à longo prazo, são necessários mais estudos que consigam abranger a trajetória de todas as manifestações depressivas envolvidas no reganho de peso, em condições que uma é dependente da outra (ALYAHYA; ALNUJAIDI, 2022;SCHACHTER et al, 2018). Em alguns casos, a perda de peso abaixo do ideal após a cirurgia bariátrica está associada com alimentação compulsiva, transtornos alimentares, ansiedade e depressão.…”
Section: Resultsunclassified
“…À longo prazo, estas medidas ampliam a redução de peso aumentando a eficácia da cirurgia e melhoram a qualidade de vida. Entretanto, para a compreensão destes efeitos à longo prazo, são necessários mais estudos que consigam abranger a trajetória de todas as manifestações depressivas envolvidas no reganho de peso, em condições que uma é dependente da outra (ALYAHYA; ALNUJAIDI, 2022;SCHACHTER et al, 2018). Em alguns casos, a perda de peso abaixo do ideal após a cirurgia bariátrica está associada com alimentação compulsiva, transtornos alimentares, ansiedade e depressão.…”
Section: Resultsunclassified
“…Therefore, although bariatric surgery is considered by many to be the most effective obesity treatment, there is already evidence that proves a high prevalence of depressive symptoms and suicidal ideation in patients after the procedure. According to the literature, the persistence of both conditions after surgery may be associated with weight regain, eating disorders, and quality of life in these individuals [ 55 , 56 ]. It is suggested, from this, that the most indicated in this case would be to conduct a complementary evaluation, and possible intervention, about the presence of depressive symptoms and suicidal ideation in obese patients with BED before and after bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Even though it is considered one of the most effective treatments for obesity, the clinical management of bariatric surgery patients generally focuses on weight loss and improvement of obesity-related conditions. However, a satisfactory result of the method in question is also dependent on the improvement of mental health status [ 55 , 56 ]. In addition, it is suggested that the patient undergo a mental health assessment before and after the patient undergoes surgery.…”
Section: Discussionmentioning
confidence: 99%
“…À longo prazo, estas medidas ampliam a redução de peso aumentando a eficácia da cirurgia e melhoram a qualidade de vida. Entretanto, para a compreensão destes efeitos à longo prazo, são necessários mais estudos que consigam abranger a trajetória de todas as manifestações depressivas envolvidas no reganho de peso, em condições que uma é dependente da outra (ALYAHYA; ALNUJAIDI, 2022;SCHACHTER et al, 2018).…”
Section: Discussionunclassified